Comparing numerical method for the solution of epidemic model / Mat Salim Selamat - Selamat, Mat Salim (2006)
In this paper, the Adomian Decomposition Method (ADM) is applied to the epidemic model for non-fatal disease which is a three dimensional system of non linear ordinary differential equations. The size of population is assumed constant over the period of the epidemic. Comparison between the decomposition solutions and the classical Runge-Kutta (RK4) numerical solutions are made.